2020
DOI: 10.1007/s11145-020-10039-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of instruments to measure Portuguese third graders’ reasons to write and self-efficacy

Abstract: There is a growing body of research showing that writers are influenced by motivation-related aspects. This study documents the translation process of the Portuguese version of the Writing Motivation Questionnaire and the construction of two scales to measure self-efficacy for handwriting and story writing. The psychometric properties of these instruments were then explored. Firstly, we examined the factorial structure of these instruments and tested measurement invariance across two independent samples of 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…To increase the ratio of predictors to participants and consequently the power of the regression analyses, instead of the six motives to write, we used two average-based composite scores. Based on Deci and Ryan (1985) and Limpo et al (2020), curiosity, emotional regulation, and relief from boredom factors were grouped into a "intrinsic motives" variable (α = .80 for Grade 6, α = .89 for Grade 7), whereas competition, grades, and social recognition were grouped into a "extrinsic motives" variable (α = .75 for Grade 6, α = .76 for Grade 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase the ratio of predictors to participants and consequently the power of the regression analyses, instead of the six motives to write, we used two average-based composite scores. Based on Deci and Ryan (1985) and Limpo et al (2020), curiosity, emotional regulation, and relief from boredom factors were grouped into a "intrinsic motives" variable (α = .80 for Grade 6, α = .89 for Grade 7), whereas competition, grades, and social recognition were grouped into a "extrinsic motives" variable (α = .75 for Grade 6, α = .76 for Grade 7).…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be related with participants’ age. Ng et al (2021) targeted elementary school, in which these yet-to-be-acquired basic skills and associated self-efficacy may have a more prominent role in the writers’ motivation (Limpo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the limited amount of SDT research on reading and writing motivation, some studies focused on the development of domain-specific self-report measures ( Guay et al, 2010 ; De Naeghel et al, 2012 ; De Smedt et al, 2018b ; Rocha et al, 2019 ; Limpo et al, 2020 ). For instance, De Naeghel et al (2012) , developed and validated the Self-Regulation Questionnaire-Reading Motivation (SRQ-Reading Motivation), which is a reliable and valid questionnaire to measure fifth and sixth-graders’ reading motivation in both academic and recreational contexts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Contrary to expectations, Limpo, Vigário, et al (2020) found intrinsic motives for writing were lowered as a result of handwriting instruction, and Guay et al (2010) reported primary grade students placed similar emphasis on intrinsic and autonomous motives for writing. Multiple studies have demonstrated that intrinsic, extrinsic, and self-regulatory motives are separable constructs, and these writing motives predict writing achievement and writing efficacy of typically developing writers (Graham et al, 2022; Limpo, Filipe, et al, 2020; Ng et al, 2021, 2022; Rocha et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%